Race trouble: Attending to race and racism in online interaction. (1st April 2014) - Durrheim, Kevin; Greener, Ross; Whitehead, Kevin A.
<x xml:space="preserve">Abstract</x> This article advocates the concept of race trouble as a way of synthesizing variation in racial discourse, and as a way of studying how social interaction and institutional life continue to be organized by conceptions of 'race' and 'racism'. Our analysis of an online discussion at a South African University about the defensibility of a characterization of (black) student protesters as 'savages' revealed a number of familiar strategies: participants avoided explicit racism, denied racism, and denied racism on behalf of others. However, the aim of this analysis was not to identify the 'real' racism, but to show how race and racism were used in the interaction to develop perspectives on transformation in the institution, to produce social division in the University, and to create ambivalently racialized and racializing subject positions. We demonstrate how, especially through uses of deracialized discourse, participants' actions were observably shaped by the potential ways in which others could hear 'race' and 'racism'. Race trouble thus became manifest through racial suggestion, allusion, innuendo, and implication. We conclude with a call to social psychologists to study the ways in which meanings of 'race' and 'racism' are forged and contested in relation to each other.